PENGARUH KUALITAS LAYANAN DAN PERSEPSI HARGA TERHADAP KEPUASAN PELANGGAN PADA MASKAPAI PENERBANGAN TIGER AIR MANDALA - Harjati, Lily; Venesia, Yurike (L2Dikti Wilayah III, 2017)
With increased rapid transportation industry now makes competition between companies is getting tight in snatch customers as well as maintain existing market share. The good company’s service and pricing is a unity that can be seen from the customer's expectations.Therefore service companies should continue to seek customer satisfaction in particular with the quality of service and the best price which is the overall impression upon performance of the company. The objective of this research are to (1) quality of service TigerAir Mandala, (2) Customer Price Perception in TigerAir Mandala, (3) The TigerAir Mandala’s customer satisfaction, (4) the influence of the quality of service and Price Perceptions towards customer satisfaction of TigerAir Mandala. The method used is the judgment sampling with a respondent of 100 people who have used the TigerAir Mandala.. The results showed that: (1) the level of quality of services provided to the customers of the Mandala TigerAir is good. (2) the customer agrees that the perception the price against the TigerAir Mandala is in accordance with the details of the questions on the questionnaire. (3) Customer TigerAir Mandala satisfied service quality and prices will be given to the customer, (4) the quality of service and Price perceptions of positive and significant effect against customer satisfaction in TigerAir Mandala.